Analysis of swimming technique: state of the art: Applications and implications. - Sanders, R.; Psycharakis, S.; McCabe, C.; Naemi, R.; Connaboy, C.; Li, Shuping; Scott, G.; Spence, A. (Biomechanics and Medicine in Swimming X, 2006)
CONCLUSION This paper described how 'state of the art' video equipment and videobased methods are being applied to assist analysis and research in swimming at the Centre for Aquatics Research and Education. Applications ranging from qualitative analysis for immediate feedback to 3D analysis to advance knowledge of how performance is optimized were presented.